2017
DOI: 10.1016/j.tsf.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity patterns induced by phase-separation in polymer blend films

Abstract: Systematical studies on the impact of the thickness of thin films composed of polystyrene (PS) or poly(ethylene oxide) (PEO) on the effective elasticity of polymer-decorated soft polydimethylsiloxane substrate were performed. For both investigated polymer films, elasticity parameter was determined from force-displacement curves recorded using atomic force microscopy. Effective stiffness of supported film grows monotonically with film thickness, starting from the value comparable to the elasticity of soft suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Polymeric substrates comprising local mechanical stiffness pattern or nanostructural features are intensively investigated in the context of applications such as haptic displays (touchpads), stretchable electronics, mechanical and optical data storage devices, [1][2][3][4][5][6][7][8] or as instructive cell substrates guiding mechanosensitive (stem) cells. [9][10][11][12][13][14][15] While individual cells can react to structural features of few nanometers in size and mechanical differences in the Pascal (Pa) range, [9,14] the tactile sensitivity of a human finger is only capable of detecting structural features above 10 nm and local mechanics in the kPa regime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymeric substrates comprising local mechanical stiffness pattern or nanostructural features are intensively investigated in the context of applications such as haptic displays (touchpads), stretchable electronics, mechanical and optical data storage devices, [1][2][3][4][5][6][7][8] or as instructive cell substrates guiding mechanosensitive (stem) cells. [9][10][11][12][13][14][15] While individual cells can react to structural features of few nanometers in size and mechanical differences in the Pascal (Pa) range, [9,14] the tactile sensitivity of a human finger is only capable of detecting structural features above 10 nm and local mechanics in the kPa regime.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] While individual cells can react to structural features of few nanometers in size and mechanical differences in the Pascal (Pa) range, [9,14] the tactile sensitivity of a human finger is only capable of detecting structural features above 10 nm and local mechanics in the kPa regime. [16][17][18][19][20] Mechanically patterned surfaces can be realized by variation of the polymer's chemical composition (e.g., phase separated blends) [2] or crosslinking density (e.g., hydrogels). [9,21] Another approach is based on placing rigid microstructures or defined closed cavities (pores) [22] under soft/elastic polymeric materials and applying pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness of the substrate is known to impact adhesion and proliferation of cells [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Our previous research, performed for PDMS elasticity changing stepwise from 600 kPa to 1.5 MPa, showed that substrate stiffness affects the behavior of normal and IPF-derived fibroblasts, influencing the number, shape, and arrangement of cells after 72 h culturing [ 35 ].…”
Section: Discussionmentioning
confidence: 99%